2015
DOI: 10.1080/15295192.2015.1065120
|View full text |Cite
|
Sign up to set email alerts
|

Ebb and Flow in Parent-Child Interactions: Shifts from Early through Middle Childhood

Abstract: Objective This study documents the strength of relations between key parent and child behaviors as they occur during typical encounters for both mothers and fathers and determines whether there were shifts in the strength of relations between parent and child behaviors during early and middle childhood. Design Multivariate multi-level modeling was used to examine associations between three parent behaviors (respect for autonomy, stimulation of development, hostility) and two child behaviors (agency, negativi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 88 publications
1
11
0
Order By: Relevance
“…At different developmental stages, children need customized stimulation and guidance adapted to the situation, their needs, and the task at hand (Bradley, Pennar, & Iida, 2015). A recent study in 4-to 11-year-olds demonstrated that the relationship between parenting behaviors and child agency shifts with age (Bradley et al, 2015), in line with the findings of Landry and colleagues (2000), Cuevas and colleagues (2014), and Mathis and Bierman (2015).…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…At different developmental stages, children need customized stimulation and guidance adapted to the situation, their needs, and the task at hand (Bradley, Pennar, & Iida, 2015). A recent study in 4-to 11-year-olds demonstrated that the relationship between parenting behaviors and child agency shifts with age (Bradley et al, 2015), in line with the findings of Landry and colleagues (2000), Cuevas and colleagues (2014), and Mathis and Bierman (2015).…”
mentioning
confidence: 60%
“…At different developmental stages, children need customized stimulation and guidance adapted to the situation, their needs, and the task at hand (Bradley, Pennar, & Iida, 2015). A recent study in 4-to 11-year-olds demonstrated that the relationship between parenting behaviors and child agency shifts with age (Bradley et al, 2015), in line with the findings of Landry and colleagues (2000), Cuevas and colleagues (2014), and Mathis and Bierman (2015). Since AC and EF skills are considered crucial in goal-directed behavior (Giesbrecht et al, 2010) and rapid improvements in AC and EF skills occur between the ages four and eight (Best & Miller, 2010), this raises the question whether key aspects of parenting strategies are related to AC and EF, and to what extent age moderates this relationship in 4-to 8-year-olds.…”
mentioning
confidence: 99%
“…Last, the study did not investigate father–child relationship. Previous studies have shown that the relationship that a child has with his/her mother and father is different ( Bradley et al, 2015 ), which means that the examination of father–child relationships can provide a holistic picture of the Jamaican parent–child relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The normative patterns of expression and association of infant behaviours and maternal parenting practices, as they occur in dyadic involvement in everyday situations, have farreaching implications for biological and developmental theory and research, as well as clinical practice and social policy. Because it embraces a wider selection of samples and analyses infant and mother activities in a detailed way, this investigation may advance theory, help guide fresh research about early human development, and inform programmes aimed at improving parental caregiving and child well-being [50]. On the basis of these findings, biological, behavioural and clinical scientists may formulate more accurate accounts of how parents and infants interact in everyday situations to promote or hinder children's wholesome development.…”
Section: (C) Correspondences Between Behaviours Of Infants and Parentmentioning
confidence: 99%